Modelling and simulation of train schedule and operation - Mat Ripin, Mohd Khairi Haslamia (2015)
A modelling and simulation study was carried out to examine the current performance of train scheduling and operation of Keretapi Tanah Melayu Berhad (KTMB). The objectives of this study were to measure the performance of KTMB operation according to the current schedule and available resources by build a model that can simulate the operation. Also to evaluate alternative to increase the performances of KTMB train schedule and operation. Simulation software named Arena was used in this study to build the models and simulate various situation. Three situations and conditions of the current system were modeled and simulated in Arena to understand the current performance of the system. The simulation results revealed that the current scheduling and operation was below the level of their actual capabilities. To increase the performance of their scheduling and operation, new and improved simulation models was developed. The models was improved by adding new ETS trains to the system and provide more choice of trip to the passengers. After the improvement, simulation result shows some increment to their performance. Their utilization can be increased up to 16.36% of improvement. With the new scheduling and operation system, more passenger can be served and more travel option by travel time can be offered. This can attract more customers and directly can give positif impact to the revenue of the company.